Hizbullah's identity construction - Alagha, Joseph Elie (Amsterdam University Press, 2011)
"The important study offers a revolutionary new perspective on the political phenomenon of Hizbullah whose evolution has frequently confounded scholars and politicians. Drawing on his unparalleled access to primary sources, Alagha has produced a unique work which traces all the shifts in Hizbullah's construction and reconstruction of its identity."--Publisher's site.